La cruzada de Fodor y Lepore contra el holismo de Quine. Protesta de un comprador inconforme - Ávila, Ignacio (2002)
“The Crusade of Fodor and Lepore against Quine’s Holism. Protest of an Shopper Dissatisfied”. In this paper I discuss Fodor and Lepore’s arguments against Quinean semantic holism. I argue that Fodor and Lepore do not examine the more conclusive Quinean arguments in favor of this thesis. Then I point out that they misunderstand the Quinean articulation between epistemological holism, verificationism and semantic holism. Lastly, I suggest that the attack of Fodor and Lepore to Quine’s semantic holism tacitly presupposes a certain non epistemic atomism.